2021
DOI: 10.5194/acp-2021-329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exploring the uncertainties in the aviation soot-cirrus effect

Abstract: Abstract. A global aerosol-climate model, including a two-moment cloud microphysical scheme and a parametrization for aerosol-induced ice formation in cirrus clouds, is applied in order to quantify the impact of aviation soot on natural cirrus clouds. Several sensitivity experiments are performed to assess the uncertainties in this effect related to (i) the assumptions on the ice nucleation abilities of aviation soot; (ii) the representation of vertical updrafts in the model; and (iii) the use of reanalysis da… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…8) the ICNC are reduced (by 30 % at 250 hPa, although with large variability), while no visible effect is found for CDNC. These results are in line with those obtained by Righi et al (2021), who showed that aircraft emissions do increase ice crystal number concentration, although their results were not statistically significant. The ice crystal effective radius seems to be the least affected by the reduced emissions during the COVID-19 lockdown, with a negligible absolute and relative difference.…”
Section: Aerosol-cloud Interactionssupporting
confidence: 92%
“…8) the ICNC are reduced (by 30 % at 250 hPa, although with large variability), while no visible effect is found for CDNC. These results are in line with those obtained by Righi et al (2021), who showed that aircraft emissions do increase ice crystal number concentration, although their results were not statistically significant. The ice crystal effective radius seems to be the least affected by the reduced emissions during the COVID-19 lockdown, with a negligible absolute and relative difference.…”
Section: Aerosol-cloud Interactionssupporting
confidence: 92%
“…The same effect arises in aircraft flight tracks, where the emitted particles may act as ice nucleating particles, leading to contrail formation (Schumann et al, 2017) and an increase in cirrus cloud formation in the upper troposphere (Boucher, 1999). Still, the magnitude of the aviation soot effect on the radiation budget remains uncertain (Urbanek et al, 2018;Righi et al, 2021). Recently, satellite data have been used to quantify changes in clouds in regions with COVID-reduced airtraffic in 2020 (Quaas et al, 2021;Gettelman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Liquid-origin cirrus completely forms through heterogeneous freezing (immersion and contact freezing) and is then uplifted to the colder altitudes where homogeneous freezing can occur under high updraft conditions in addition to the heterogeneously formed ice crystals. Recently, numerous studies have reported that many types of aerosols existing at the upper troposphere (cirrus altitudes) can serve as effective ice-nucleating particles (Cziczo et al, 2013), such as aviation soot (Tesche et al, 2016;Righi et al, 2021), volcanic aerosols (Sporre et al, 2022), wildfire smoke (Ansmann et al, 2021;Hu et al, 2022), dust aerosols (Kuebbeler et al, 2014), and sulfate and nitrate particles (Che et al, 2021), making the in situ heterogeneous formation at cirrus altitudes possible.…”
Section: Introductionmentioning
confidence: 99%